Transarterial chemoembolization with rivoceranib and camrelizumab for BCLC stage C hepatocellular carcinoma - Zhu, Rui; Zhang, Zi-Xuan; Lu, Xin-Zhi; Mao, Kui (Frontiers in Oncology, 2025)
BackgroundTransarterial chemoembolization (TACE) and systemic therapy are frequently applied for advanced hepatocellular carcinoma (HCC), but their combined therapeutic potential remains uncertain. Here, the clinical efficacy and safety of TACE together with rivoceranib plus camrelizumab in Barcelona Clinic Liver Cancer (BCLC) stage C HCC were investigated.MethodsBetween January 2021 and December 2024, 167 consecutive cases of BCLC stage C HCC were retrospectively analyzed. Eighty-three received rivoceranib-camrelizumab with TACE, and 84 received rivoceranib-camrelizumab alone. Comparisons of baseline characteristics, tumor response, long-term outcomes, and adverse events were conducted.ResultsBaseline variables were balanced between groups. Combination therapy achieved significantly higher partial (39.8% vs. 20.2%, P = 0.006) and objective response rates (50.6% vs. 29.7%, P = 0.006) than systemic therapy alone. Median progression-free survival (PFS: 11.0 vs. 9.0 months, P = 0.008) and overall survival (OS: 19.0 vs. 15.0 months, P = 0.001) were both longer in the combination group. Cox regression identified combined treatment as an independent predictor of extended PFS and OS. Post-embolization symptoms occurred only in the TACE group but no grade 3-4 events were observed, and rates of systemic treatment-related adverse events were comparable between groups.ConclusionsAdding TACE to rivoceranib-camrelizumab has the potential to improve tumor response and survival in BCLC stage C HCC without compromising safety.